Immobilization and nutrient retention by pine sawdust for soilless culture. - Pineda Pineda, Joel; Sánchez del Castillo, Felipe; Moreno Pérez, Esaú del Carmen; Valdez Aguilar, Luis Alonso; Castillo González, Ana María; Ramírez Árias, Armando; Vargas Canales, Juan Manuel (REVISTA TERRA LATINOAMERICANA, 2019)
Pine (Pinus sp.) sawdust has been used as a growing medium for the cultivation of vegetables and ornamentals. In the present work the objective was to assess the immobilization or retention of N, P, K, and Ca in pine sawdust as the main substrate component by applying Steiner nutrient solution at different concentrations (20, 30 and 40 meq L-1). We used uncomposted sawdust, alone or in mixtures (70/30, v/v) with volcanic tuff of different particle sizes (fine ≤ 3 mm, medium 3-6 mm, and coarse 6-12 mm). For two months, leachate was collected daily, and every 10 days, the average concentrations of N, P, K, and Ca, as well as pH and electrical conductivity (EC) were measured. The effect of the interaction substrate × nutrient solution concentration on N, P, K and Ca in the leached water was observed. These nutrients increased in concentration in the leachate water in accord with the nutrient solution concentration and as the diameter of volcanic tuff particles diminished. Irrigation with 20 meq L-1 (2 dS m-1) concentration of nutrient solution reduced the concentration of N, P, K, and Ca in leached water below its concentration in the supplied nutrient solution, while irrigation with 30 or 40 meq L-1 (2 or 4 dS m-1) resulted in similar concentration in leached water up to 20 or 30 dat, but at 40 dat, concentration of these nutrients in the leached water was higher. Immobilization of N and P, K, and Ca retention in the sawdust substrate occurred during the first 40 ddt, related to an increase in pH (up to 8.6), a decrease in EC (until 0.5 dS m-1) and low concentrations of N, P, K, and Ca in the leached water.